Islamologi Terapan dan Problema Aplikasinya: (Mengkaji Pemikiran Mohammed Arkoun) - Baedhowi Baedhowi (Al-Jami'ah Research Centre, 2003)
This article is trying to elaborate Arkoun's thought on the applied Islamology, which is an effort to evaluated, develop and activates some deficiencies of Western traditional islamology. In Arkoun's point of view, the studies of classical islamology are so rigid and inflexible. They tend to restrict their studies on certain and selected works of Islam, so their works are not empirical, unfruitful, could not answer the Muslims need in the contemporary world. Therefore, the applied islamology should leave the shackle of classical episteme of medieval era that is colored by romanticism in the past and develop to toward the modern episteme with the religious anthropological tool. The problem is how to link the methodological and Epistemological gap between Islamic thought that has been cut from its old tradition and the progressive modern thought. To link this gap, according to Arkoun, the bath should be dealt with by applied islamology, i.e., al-turāth (tradition or cultural heritage) and modernity.